JMP Start Statistics, 5th Edition - Sall, John; Creighton, Lee; Lehman, Ann; Stephens, Mia (SAS Institute, 2012)
Updated for JMP 10, the book provides hands-on tutorials with just the right amount of conceptual and motivational material to illustrate how to use the intuitive interface for data analysis in JMP. Features concept-specific tutorials, examples, brief reviews of concepts, step-by-step illustrations, and exercises.